Teachers’ Perceptions of Inadequate Outdoor Play Among Preschool Children in Aba Nigeria - Emmanuel Lucas Nwachukwu; Nwamaka Goodness Egbue; Ijeoma VictorNwakaku; Unegbu Lasbrey Ikechukwu (International Journal of Educational Development and Innovation, 2026)
This study examined preschool teachers’ perceptions of inadequate outdoor play provision in Aba, Abia State, Nigeria, focusing on availability, developmental implications, and implementation constraints. A descriptive survey design was employed. The population comprised 453 teachers in registered public and private preschools. Using multistage sampling informed by Yamane’s formula (5% margin of error), 212 questionnaires were distributed, and 200 valid responses were analyzed. Data were analyzed using descriptive statistics and chi-square tests. Results indicate that outdoor play provision is generally inadequate, characterized by limited space, restricted daily access, insufficient time allocation, and safety concerns (cluster mean = 2.26). Teachers agreed that constrained outdoor play adversely affects children’s physical activity, peer interaction, classroom behaviour, and attention regulation (cluster mean = 3.47). No significant subgroup differences were found. The findings highlight a gap between teachers’ recognition of outdoor play’s developmental importance and structural conditions shaping practice, underscoring the need to strengthen facility standards and reinforce play-based pedagogy.